Thinking through writing a guide to becoming a better writer and thinker - Kaag, John; Belle, Jonathan van (Princeton University Press, 2024)
"A concise and practical manual on developing reading, writing, and critical thinking skills in tandem For college students learning how to write on scholarly subjects, writing and critical thinking go hand in hand. And yet most books on these topics are categorized separately: writing guides and critical thinking handbooks. This book is different, offering a manual for developing reading, writing, and thinking skills in tandem. With short, practical chapters, Thinking through Writing helps readers learn to think critically about themselves and the world at large, read carefully and get the necessary literary support, write clearly and persuasively, stay on point, and finish their work as cleanly and compellingly as possible. Drawing on years of teaching critical thinking and writing, including almost a decade of teaching Harvard's freshman expository writing course, the authors invite readers to consider the intimate relationship between thinking and the creative, critical, self-actualizing act of writing. Interviews with some of the most interesting and brilliant writers working today Advice on how to structure an argument, write for an audience, work through writer's block and anxiety, and much more Tips on how to make your writing unique and personal Exercises and templates to help novice writers reach their full potential in practice"-- Provided by publisher.